Dress, dementia and the embodiment of identity. (May 2013) - Twigg, Julia; Buse, Christina E
The article explores the significance of dress in the embodied experience of dementia, exploring questions of identity, memory and relationship. It suggests that clothing and dress are important in the analysis of the day-to-day experiences of people with dementia, giving access to dimensions of selfhood often ignored in over-cognitive accounts of being. As a result clothing and dress can be significant to the provision of person-centred dementia care. These arguments are explored through ideas of embodied identity, the materialisation of memories, and the maintenance, or otherwise, of appearance in care. The article forms part of the background to an ESRC-funded empirical study exploring the role of clothing and dress in the everyday lives of people with dementia, living at home or in care homes, and of their relatives.